Changes in the morbidity and costs of systemic lupus erythematosus in Poland in the years 2008–2012 - Śliwczyński, Andrzej (Reumatologia, 2015)
OBJECTIVES: The goal of the article is to present the changes in morbidity and costs of systemic lupus erythematosus (SLE) in Poland in the 2008–2012 period, depending on the province of residence of the patients based on data reported to the public payer – the National Health Fund. MATERIAL AND METHODS: Based on the ICD-10 code and the patient's personal identity number, the number of patients and medical costs (cost of hospitalization, pharmaceutical, medical procedures, dialysis and specialist consultations) were calculated by province (voivodeship) and urban or rural residence. RESULTS: Annually on average in the assessed period in Poland approximately 20 000 patients were diagnosed with SLE. The studied group was dominated by women (they were 5.2 times more numerous). The morbidity rate was 52.183 patients per 100 thousand inhabitants. Most patients were in the age range of 48–56 years. Average annual expenses for this group of patients over the examined period were USD 16,327 million. Two times more was expended on patients inhabiting cities, approximately 4 times more on women. Calculated per patient, the average cost of therapy was USD 810.63. CONCLUSIONS: The population of SLE patients in Poland is highly stable. The results of analysis indicate 1.64 times more frequent occurrence in urban areas, which may be connected with availability of doctors. The SLE treatment costs in Poland are much lower than in other countries, which is related mainly to the fact that therapy with biological drugs is not financed.